O16-4 An integrated approach to infection and respiratory illness prevention in home healthcare: preliminary results of the safe home care cleaning and disinfecting study. (1st September 2016) - Quinn, Margaret; Markkanen, Pia; Galligan, Catherine; Sama, Susan; Gore, Rebecca; Goodyear, Nancy; Brouillette, Natalie; Kriebel, David; Lindberg, John; Vega, Alexis Parker; Sheikh, Noor; Karlsson, Nicole
Abstract : Objectives: While cleaning and disinfecting (C&D) are essential for infection prevention (IP) in healthcare, there is increasing evidence that C&D chemicals cause occupational respiratory illness. An international working group (WG) on C&D in healthcare was engaged by the U.S. National Institute for Occupational Safety and Health to identify research needs to develop an integrated framework for effective IP and occupational health (OH) protection for healthcare workers (Quinn, WG Co-Chair). This presentation describes the WG and a study of C&D among home care (HC) aides which was guided by WG recommendations. Study objectives were to: 1) identify the extent to which C&D is performed by HC aides, 2) assess C&D respiratory hazards, and 3) compare the effectiveness of conventional versus "green" C&D products to reduce pathogens in the home environment. Methods: HC aides completed a survey including questions about C&D product use and respiratory hazards occurring during their HC visits. In an environmental laboratory, airborne exposures from C&D products were assessed during simulated cleaning tasks. In a microbiology laboratory, cleaning effectiveness (removal of soil) and disinfection effectiveness (reduction in microorganisms) on common household surface materials were compared using bleach, a "green" product, and a do-it-yourself (DIY) mixture. Results: The survey population included 1, 249 HC aides contributing information on 3, 484 HC visits. Aides performed C&D in 80% of their visits. Bleach was used in 25% of visits; an additional 15% used other irritant chemicals. Environmental assessment of C&D products showed volatile organic compounds emitted from all products; peak exposures to chlorine could exceed occupational exposure limits. Microbiology assessment found that bleach and a "green" product effectively removed soil and reduced E. coli and S. aureus; the DIY mixture was less effective. Conclusions: An integrated IP-OH approach to assessing C&D exposures, as recommended by the WG, can provide more comprehensive prevention strategies.